MENGIDEALISASIKAN PENAMPANG LINTANG BULUH BAMBU MENJADI BENTUK GEOMETRI CONIC UNTUK MENGHITUNG SIFAT PENAMPANGNYA - Effendi Tri Bahtiar; Asep Denih; Lina Karlinasari; Gustian Rama Putra; Naresworo Nugroho; Sulistyono (BRIN Publishing, 2022)
A designer needs to simplify the bamboo cross-section shape variation to the closest standard geometry so a structural analysisof bamboo construction can be carried out. Bamboo culm’s cross-sectional geometrics vary and may be similar to conic such as acircle, ellipse, or egg-shape ring. The best-fit conic section, which is the most similar to the actual geometric shape of the bambooculm’s cross-section, should be considered. This study formulates mathematical equations for calculating the bamboo culm’s crosssectional properties (including the area, the first moment of area, the centroid, and the moment of inertia), which are fitted by acircle, ellipse, and egg-shaped ring. The thickness, diameter, major axis, and minor axis of four bamboo species (i.e., Gigantochloaapus, Bambusa vulgaris, Gigantochloa pseudoarundinacea, and Gigantochloa robusta) were measured, and thosevalues were substituted into the equations to produce the range of cross-sectional properties of each species.